ARIK UMI PUJIASTUTI - admin, Keguru (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2019)
AbstractThe objectives of this study are: 1) to describe the implementation of the SpecialAdvisory Teacher (GPK) roles and duties on inclusive education of all of stateElementary Schools in Soko, Tuban on process of identifying types of needs, assessment,and compiling individual learning programs, 2) to describe the implementation of GPKroles and duties related to the designing process and giving specific programs, and 3) todescribe the implementation of GPK roles and duties in modifying teaching materials.The research method is qualitative descriptive. The data collection instruments used areinterviews and field notes. The results of this study are, 1) the role and duties of SpecialAdvisory Teacher (GPK) at inclusive education on the process of identifying needs,assessment, and compiling individual teaching programs that run less than optimalbecause the lack of resources, 2) in the designing process and giving specific programsthat must be carried out by Special Advisory Teacher (GPK) does not run optimally dueto differences in perceptions between GPK in giving specific programs to the needs ofABK, 3) in the implementation of GPK role in modifying teaching materials , actually ithasn?t run well. It because the lack of resources and funds sources. Based on the resultsof the study, the implementation of GPK roles and duties in identifying types of needs,assessment, preparation of individual learning programs, designing learning, givingspecific programs, and modifying teaching materials were not optimal. As for the lack ofoptimal implementation of GPK roles and duties due to lack of resources (GPK), lack ofsocialization regarding the roles and duties of GPK, and regulations related to mainduty ann functions from GPK